Combination Cancer Immunotherapy: Immunogenic Cell Death Inducing Fluorinated Mitochondria‐Disrupting Helical Polypeptide Synergizes with PD‐L1 Immune Checkpoint Blockade (Adv. Sci. 7/2021). Issue 7 (7th April 2021) - Jeong, Seong Dong; Jung, Bo‐Kyeong; Ahn, Hyo Min; Lee, DaeYong; Ha, JongHoon; Noh, Ilkoo; Yun, Chae‐Ok; Kim, Yeu‐Chun
Abstract : In article number 2001308, Chae‐Ok Yun, Yeu‐Chun Kim, and co‐workers develop endoplasmic reticulum (ER) stress‐mediated immunogenic cell death (ICD) inducing fluorinated mitochondria‐disrupting helical polypeptides (MDHPs). These helical polypeptides destabilize the mitochondrial outer membrane, leading to the overproduction of intracellular reactive oxygen species (ROS) and ICD. In addition, co‐treatment of fluorinated MDHP and anti‐Programmed death‐ligand 1 antibodies (αPD‐L1), which block PD‐L1 on tumor cell, significantly regresses tumor growth by activating the cytotoxic T cell response.